A Modified Stoppa (Technique) Approach for Treatment of Pediatric Acetabular Fractures. (27th May 2013) - Elmadag, Mehmet; Acar, Mehmet Ali
Abstract : Pediatric acetabular fractures are rare, and anterior column fractures are even rarer. Generally, conservative treatment is applied. If there is displacement of more than 2 mm or findings of instability or fragments within the joint, then surgical treatment is applied. Anterior and posterior approaches may be used in surgical treatment. With pediatric patients, even greater care should be taken in the choice of surgery to be performed according to the fracture pattern to avoid postoperative triradiate cartilage damage. Therefore, minimally invasive surgery is more appropriate. We herein present a case of an acetabulum anterior column posterior hemitransverse fracture following a traffic accident, which was treated surgically using a modified Stoppa (technique) approach.